Forced Empowerment and the Paradox of Mobile Dating Apps. (December 2021) - Sobieraj, Sabrina; Humphreys, Lee
New women-focused mobile dating apps purport to empower women by having them "make the first move" and disrupt traditional male-dominated dating norms. Drawing on feminist approaches and technological affordances, we examine how heterosexual cisgender women and men experience this "empowerment" and contrast it to other mobile dating app use. We used a multimethod approach to conducting app walkthroughs, focus groups, and interviews to contrast the mobile dating apps, Tinder and Bumble. The findings reveal that perceptions of free choice and action determine empowerment experiences. Our study reveals that the "forced empowerment" on Bumble was still strongly shaped by heterosexual gender norms that encouraged "good" girls and guys to use the app to look for long-term relationships but continue to use Tinder to hook up, despite the popular misogyny on Tinder identified by both men and women in our study. We conclude by discussing the empowerment paradox of dating apps through popular feminism and misogyny.